Serum-free thyroxine concentrations, measured by chemiluminescence assay before and after thyrotropin administration in healthy dogs, hypothyroid dogs, and euthyroid dogs with dermathopathies. - Paradis, M (1996)
The purpose of this study was to determine the usefulness of free thyroxine (FT4) measured by chemiluminescence in evaluating thyroid function in dogs. Total thyroxine (TT4) concentration measured by radioimmunoassay (RIA) and FT4 measured by chemiluminescence were evaluated in 30 healthy dogs, 60 euthyroid dogs with concurrent dermatopathies, and 30 hypothyroid dogs before and after intravenous stimulation with 1 or 2 IU of thyrotropin (TSH). Median basal TT4 and median TT4 concentrations at 4 h post-TSH administration were not significantly different (P < 0.0001) between healthy dogs and euthyroid dogs with dermatopathies, but were significantly higher than those in hypothyroid dogs. In healthy dogs, the median TT4 concentrations at 4 and 6 h post-TSH administration were not significantly different. Median basal FT4 and median FT4 concentrations at 4 h post-TSH administration in healthy dogs were significantly lower (P < 0.0001) than those in euthyroid dogs with dermatopathies, but significantly higher than the same parameters in hypothyroid dogs. There was a significant difference between the median FT4 concentrations at 4 h post-TSH administration and median basal FT4 concentrations for healthy dogs and euthyroid dogs with dermatopathies, but not for hypothyroid dogs. Lastly, in healthy dogs, median FT4 concentrations at 4 and 6 h post-TSH administration were not significantly different. Free thyroxine measured by chemiluminescence was highly correlated (P < 0.0001; Spearman r = 0.91) with FT4 measured by the reference method for free hormone analysis, namely, equilibrium dialysis, when sera from 56 dogs were used.